The Effectiveness of the Dhuha Prayer Program in Improving Discipline and Religiousness at State Elementary School Kwaron 1 - Ahmad Khotim (LP3M STAI At-Tahdzib Jombang, 2026)
Dhuha prayer mentoring is an effort to develop the character of students at State Elementary School Kwaron 1, through a Participatory Action Research (PAR) approach. This study aims to explore and understand the impact of Dhuha prayer practices on the development of students’ discipline and religious character, including attitudes of responsibility, and other spiritual values. Students involved in this program showed an increase in discipline, enthusiasm, and responsibility towards worship and schoolwork. In addition, Dhuha prayer activities can also strengthen social bonds between students, creating a more harmonious and conducive learning environment. The results of the study indicate that regular and consistent Dhuha prayer mentoring can increase students’ religious awareness and improve their behavior and morals in academic and social contexts. Students involved in this program showed an increase in discipline and responsibility towards worship and schoolwork, so this can trigger students’ enthusiasm for learning at State Elementary School Kwaron 1.